Republic of Mozambique : Staff Report for the 2003 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2004)
Mozambique's performance under the authorities' program during the first three quarters of 2003 continued to be satisfactory. The discussions focused on the macroeconomic policies for 2004-06 and the government's plans to address pending structural reforms to broaden and sustain growth and further reduce poverty. Discussions on structural issues concentrated on the authorities' plans to remove a number of obstacles to private sector development. A strengthened monetary and exchange rate management will be essential in Mozambique, particularly in view of the high degree of dollarization.